THE APPLICATION OF MULTI-LEADERSHIP STYLES IN STEERING AN ORGANISATION FROM CRISIS TO BUSINESS EXCELLENCE - Appiah, Isaac Onasis Osei (Global journal of Business and Integral Security, 2022)
There are many leadership styles, but this research paper sought to demonstrate how multi- leadership principles (Transformational and Servant leadership) approach could be employed in resolving real life industrial or corporate problems. That could aid in steering an organization from crisis and various organizational changes to business prosperity and excellence. These two leadership styles according to most research works done on them, are superior evolutions of the leadership development theories, very influential and effective in making the requisite positive impact on groups and organizations and hence their consideration. In conducting this research, a combination of mainly qualitative (meetings, calls and interviews) and quantitative (customer satisfaction survey) methods would be employed in a case study approach of a Mining Service Provider, a Laboratory in Africa. The goal of the paper is to investigate, demonstrate and establish that the application of right leadership and its right approach, thereof, is instrumental in solving various organizational challenges and therefore, enabling and ennobling organizational success. The study could increase the knowledge base in both academia and the corporate world. And this study will also further advance research into leadership, especially, in its practical application in business organization for maximum and positive results. The study confirmed that Transformational and Servant leadership strategies were adequate and effective in solving the organization’s problems. The application of the two leadership principles saved the laboratory, a contract amounting to about 3.6 million USD per annum in revenue and the Mine from potentially losing several millions of dollars, up to over 600 million USD per annum in revenue. The multi-leadership application secured the laboratory’s contract, made the Mine very happy and regain confidence in the laboratory. The Mine extended the duration of the contract, increasing sample volumes and scope of testing. At the same time, the multi-leadership style application took the laboratory’s financial fortunes from deep red to deep blue, consistently, continuously, and incrementally. The future financial prosperity of the laboratory looked even more promising.